A critical review of dietary laws in Judaism - Hewamanage, Wimal (My University, 2016)
In this article, the author has already discussed laws in Judaism, that are the key dietary laws in Judaism, commentary of dietary laws, vegetarianism and Judaism, the slaughterhouse, and why there are special laws in Judaism. As a religion, contained; a great history, literature, culture and ritualistic customs it shows its identity among other world religions. Having vegetarian food has been appreciated in Judaism in its early history like other world religions. As the second step, it has been allowed for vegetarian and non-vegetarian food introducing some ethical instruction on the subject of kosher food, laws of ritual slaughter, slaughterer, torn apart for eating living beings. This can be considered as a norm in Judaism.
Keywords: culture; dietary laws; judaism; literature; religion